PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBANTUAN NEARPOD TEMA 6 SUBTEMA 3 SISWA KELAS IV SD NEGERI 054870 TANJUNG JATI T.A 2022/2023 - Eti Muliani; Riza Dwina Br Ginting (JURNAL HANDAYANI PGSD FIP UNIMED, 2023)
The purpose of this study was to determine the feasibility of using interactive learning media assisted by Nearpod lesson web, and to determine the practicality of using interactive learning media assisted by Nearpod lesson web, as well as to determine the effectiveness of using interactive learning media assisted by Nearpod lesson web. The ADDIE model consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation which is used in this type of research. The population in this study were 60 people and the sample used was 30 students. The subjects of this study were fourth grade students at SD Negeri 054870 Tanjung Jati. In this study the data collection techniques used were interviews, questionnaires, tests, and documentation. Qualitative and quantitative approaches are used in data analysis techniques. The results of the research on fourth grade students of SD Negeri 054870: (1) There is a very decent qualification of 92% for the feasibility test of learning media by material experts, for media experts it is 85% (2) there is a very decent qualification of 95% for the practicality test of learning media by the teacher (3) there is a difference between student learning outcomes after using the nearpod lesson with an average value of 91.34 and students who do not use the nearpod lesson of 65. It can be concluded that the interactive learning media assisted by the Nearpod lesson web used in this study is very influential, effective, practical in the process of teaching and learning in the classroom.Keyword: Development, Learning Media, Nearpod Tujuan dari penelitian ini adalah untuk mengetahui kelayakan penggunaan media pembelajaran interaktif berbantuan Nearpod lesson web, dan untuk mengetahui praktikalitas penggunaan media pembelajaran interaktif berbantuan Nearpod lesson web, serta untuk Mengetahui efektivitas penggunaan media pembelajaran interaktif berbantuan Nearpod lesson web. Model ADDIE yang terdiri dari 5 tahapan, yaitu Analysis, Design, Development, Implementation, Evaluation yang digunakan dalam jenis penelitian ini. Populasi dalam penelitian ini sebanyak 60 orang dan sample yang digunakan sebanyak 30 orang siswa. Subjek penelitian ini adalah siswa kelas IV SD Negeri 054870 Tanjung Jati. Pada penelitian ini teknik pengumpulan data yang digunakan adalah teknik wawancara, angket, tes, dan dokumentasi. Pendekatan kualitatif dan kuantitatif digunakan pada Teknik analisis data. Hasil penelitian pada siswa kelas IV SD Negeri 054870: (1) Terdapat kualifikasi sangat layak 92 % untuk Uji kelayakan media pembelajaran oleh ahli materi, untuk ahli media sebesar 85% (2) terdapat kualifikasi sangat layak 95 % untuk Uji kepraktisan media pembelajaran oleh guru (3) adanya perbedaan antara hasil belajar siswa setelah menggunakan nearpod lesson dengan nilai rerata 91, 34 dan siswa yang tidak menggunakan nearpod lession sebesar 65. Dapat di simpulkan media pembelajaran interaktif berbantuan Nearpod lesson web yang digunakan pada penelitian ini sangat berpengaruh, efektif, praktis dalam proses belajar mengajar di dalam kelas.Kata Kunci: Pengembangan, Media Pembelajaran, Nearpod